2017
DOI: 10.18632/oncotarget.15203
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha is a promising circulating biomarker for the development of obstructive sleep apnea syndrome: a meta-analysis

Abstract: Obstructive sleep apnea syndrome (OSAS) is a chronic inflammatory disorder. The relationship between tumor necrosis factor alpha (TNF-alpha) and OSAS has been widely evaluated, but the results thus far remain inconclusive. We thereby decided to quantify the changes of TNF-alpha between OSAS patients and controls by a meta-analysis. This study complies with the MOOSE guidelines. Two reviewers independently searched articles and abstracted relevant data. In total, 47 articles (59 studies) were analyzed, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 69 publications
1
36
0
Order By: Relevance
“…As a result, they determined that inflammation indicators increase in OSAS independent of BMI [24]. In a meta-analysis, Li et al reported that circulating TNF-alpha levels were significantly higher in OSAS patients than that of the controls, and this difference became more pronounced with an increased severity of OSAS [25]. It has been determined in another study by Popko et al examining the relationship between OSAS severity and inflammation indicators that plasma IL-1 beta levels increase with apnea intensity measured by AHI [26].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they determined that inflammation indicators increase in OSAS independent of BMI [24]. In a meta-analysis, Li et al reported that circulating TNF-alpha levels were significantly higher in OSAS patients than that of the controls, and this difference became more pronounced with an increased severity of OSAS [25]. It has been determined in another study by Popko et al examining the relationship between OSAS severity and inflammation indicators that plasma IL-1 beta levels increase with apnea intensity measured by AHI [26].…”
Section: Discussionmentioning
confidence: 99%
“…In a first meta-analysis of 15 studies, it was reported that blood hsCRP levels are higher in OSA patients compared to controls and that these levels are modulated by obesity and OSA severity [78]. The second meta-analysis of 47 articles found that blood TNF-α levels are also elevated in OSA subjects [79]. Finally, the third metaanalysis of 51 studies showed that blood levels of CRP, TNF-α, IL-6, IL-8 and adhesion molecules (ICAM-1, Selectins and VCAM-1) are increased in OSA subjects [80].…”
Section: Blood-based Inflammatory Biomarkers Investigated In Osamentioning
confidence: 99%
“…It has been recently demonstrated that IHR accelerated growth and vulnerability of atherosclerotic plaque, which probably acted by triggering the activation of TLR4/NF-κB signaling [4][5][6][7]. Acting as both up-stream and down-stream mediators of TLR signaling, tumor necrosis factor (TNF)-α has been shown to be upregulated in OSA patients, and this increase became more pronounced with the more severe grades of OSAS, indicating that TNF-α might be a promising circulating biomarker for the development of OSA [8]. In vitro experiments have shown that hypoxia enhance the response of endothelial and epithelial cells to oxidative stress through potentiating monocyte-derived dendritic cell and macrophage for release of TNF-α via MAP3K8 and ERK pathways [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%